Botswana : 2006 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Authorities for Botswana. (IMF Staff Country Reports; Country Report ;, 2007)
The staff report for the 2006 Article IV Consultation on Botswana highlights economic developments and monetary and exchange rate policy. Botswana's growth has been fueled by continued increases in diamond production; and real diamond output is projected to level off, and then decline sharply after about 15 years. Diversification of the economy will require implementation of substantial structural reforms, in particular the authorities' planned reforms in labor markets, the investment environment, and the role of parastatals.